Uncovering Hippo pathway-related biomarkers in acute myocardial infarction via scRNA-seq binding transcriptomics - Xingda Li; Xueqi He; Yu Zhang; Xinyuan Hao; Anqi Xiong; Jiayu Huang; Biying Jiang; Zaiyu Tong; Haiyan Huang; Lian Yi; Wenjia Chen (Scientific Reports)
Abstract This study investigated Hippo signaling pathway-related biomarkers in acute myocardial infarction (AMI). First, differentially expressed genes (DEGs) between AMI patients and controls were identified. Consensus clustering then classified AMI subtypes, followed by subtype-specific DEG screening. Candidate genes were derived from intersecting initial DEGs with subtype-associated DEGs. Three machine-learning algorithms prioritized five biomarkers (NAMPT, CXCL1, CREM, GIMAP6, and GIMAP7), validated through multi-dataset analyses and cellular expression profiling. qRT-PCR and Western blot confirmed differential expression patterns between AMI and controls across experimental models. Notably, NAMPT, CXCL1, and GIMAP6 exhibited cell-type-specific expression in endothelial cells and macrophages. We further predicted 179 potential therapeutic agents targeting these biomarkers. Niclosamide and eugenol were observed to mitigate hypoxia-induced injury in neonatal mouse ventricular cardiomyocytes. In vivo experiments demonstrated upregulated NAMPT/CXCL1 and downregulated GIMAP6/GIMAP7 in AMI myocardial tissues, with significant NAMPT protein elevation. These biomarkers show clinical diagnostic potential and provide mechanistic insights into AMI pathogenesis.